2012
DOI: 10.1111/j.1528-1167.2012.03626.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐frequency repetitive transcranial magnetic stimulation for the treatment of refractory partial epilepsy: A controlled clinical study

Abstract: SUMMARYPurpose: This study was designed to evaluate the therapeutic effect of low-frequency repetitive transcranial magnetic stimulation (rTMS) on patients with refractory partial epilepsy. Methods: Sixty-four patients with refractory focal epilepsy were screened and 60 patients were randomly divided into two groups by stimulation intensity: 90% (group 1) or 20% (group 2) of resting motor threshold (rMT). Seizure frequency and interictal EEG epileptic discharges were compared between the baseline and follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
126
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(134 citation statements)
references
References 17 publications
3
126
3
1
Order By: Relevance
“…Проведенные исследования дали про-тиворечивые результаты. Из пяти вышеупомянутых ис-следований [115][116][117][118][119] только в двух [117,119] получены достоверные данные о снижении частоты приступов по сравнению с группой плацебо.…”
Section: эпилепсияunclassified
“…Проведенные исследования дали про-тиворечивые результаты. Из пяти вышеупомянутых ис-следований [115][116][117][118][119] только в двух [117,119] получены достоверные данные о снижении частоты приступов по сравнению с группой плацебо.…”
Section: эпилепсияunclassified
“…Among the non-invasive stimulation methods, transcranial magnetic stimulation (TMS) and repetitive transcranial magnetic stimulation (rTMS) have been used experimentally to suppress seizures in epilepsy patients [11,12]. It has been shown that applying the low-frequency high intensity rTMS on the focus of an epileptic seizure has a meaningful antiepileptic result on patients [13]. Besides, the rTMS therapy can also decrease the frequency of the epileptiform discharges, whereby improving the psychological status of these patients [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that applying the low-frequency high intensity rTMS on the focus of an epileptic seizure has a meaningful antiepileptic result on patients [13]. Besides, the rTMS therapy can also decrease the frequency of the epileptiform discharges, whereby improving the psychological status of these patients [13].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the stimuli, the coil is also found contributing to the effectiveness of TMS. According to several reports, the precise and focal targeting of the coil to the epileptogenic foci during stimulation is the prerequisite to achieve positive therapeutic results (7,10). The geometry and placement of the coil determine the activated zone of TMS in brain.…”
Section: Introductionmentioning
confidence: 99%
“…Review tion of subjects with superficial epileptogenic foci, precise and focal targeting the foci, and appropriate stimulation parameters such as frequency and intensity, which suggest the possibility to reduce the number of epileptic discharges or abnormalities with right choice of patients and methodologies (6,7,10). These studies, showing positive effects or not, are worth further expansion.…”
mentioning
confidence: 99%